Adherence to antiretroviral therapy in Jinja, Uganda: a six-year follow-up study. - Martin Mbonye; Janet Seeley; Fatuma Ssembajja; Josephine Birungi; Shabbar Jaffar (PLoS ONE, 2013)
INTRODUCTION:We report on the adherence experience of a group of people living with HIV on ART over six years in Uganda. METHODS:Between 2005 and 2009, we followed up 41 participants who were also part of a clinical trial comparing home and facility based delivery of ART in Jinja, eastern Uganda. We conducted qualitative in-depth interviews at enrolment, 3, 6, 18 and 30 months to capture experiences with adherence over time. In 2011 we returned to these participants to find out how they were fairing with long term adherence. We managed to retrace 24 participants and interviewed them about their experience. We thematically analysed the data and compared findings over time. RESULTS:Initially there were few barriers to adherence and many followed the adherence guidance closely. By year six, relaxation of these rules was noticeable although self-reported adherence continued to be high. Alcohol consumption was more common than before. Some relatives of the participants who had died claimed that some deaths were a result of alcohol. While participants reported that ART had allowed them to reclaim independence and return to work the changes in work and social routines created new challenges for adherence. Side effects like lipodystrophy were not only causing some stigma but for some tested their faith in the drugs. Many participants reported resumption of sexual lives but apart from those who selected same status partners, disclosure to new partners was minimal. CONCLUSION:Good adherence practice to ART wanes over the long-term, and people who may have disclosed at initiation find it difficult to do so to new partners once they are healthy. Further adherence interventions and support with disclosure over the course of therapy may need to be considered.